Analisis Kadar Trigliserida Pelari Berdasarkan Jenis Lari - Ni Luh Putu Pebrita Anjar Santi; Ida Bagus Rai Wiadnya; Zainal Fikri (Quality : Jurnal Kesehatan, 2017)
ABSTRAK Triglycerides are one of the fats in the body. Increased triglyceride levels occur due to obesity, alcohol consumption, and lack of activity, causing a buildup of triglycerides in the blood. Decreasing triglyceride levels can be done in various ways, one of which is to regulate lifestyle patterns such as diet regulation and physical activity. This research aimed to determine the effect of the types of running on triglyceride levels on runners. This study is a Pre-Experiment. The number of samples used was 27 people. The results of the study in the form of runner triglyceride levels were analyzed using the Wilcoxon Signed Ranks Test to see differences in the results of triglyceride levels before and after running. The results obtained from this study were before running (119,56)> after 100m run (75,11), before running (88,11)> after a 1500m run (67,22), before running (71,44 )> after running 5000m (56,33). The results of the Wilcoxon Signed Ranks Test show that the probability in the 100m and 1500m run group is (Sig) 0.008 and in the 5000m run group is (Sig) 0.007 which means that the P <Î± 0.05 value. The farther the distance a runner traveled, the greater the triglyceride level obtained by the runner. Keyword: Running type, Triglycerides